Peran Pengungkapan Sosial Berkelanjutan dalam Upaya Penanggulangan Eksploitasi Pekerja Anak: Sebuah Tinjauan Literatur - Nafi'ah, Zahra Zuhrotun; Bandiyono, Agus (Universitas Muhammadiyah Jakarta, 2025)
Object: This study aims to analyze how and why companies disclose issues related to child labor, as well as to examine the effectiveness of social disclosure in addressing the exploitation of child labor.Methodology: This research employs a literature review method by analyzing scholarly articles relevant to the topic.Findings: The findings reveal that disclosure practices concerning child labor remain limited and inadequate across various regions. Such disclosures are often driven by the desire to enhance stakeholder trust but may also serve as a form of greenwashing. The effectiveness of social disclosure in addressing child labor exploitation depends on the quality of the disclosures, support from multiple stakeholders, and the integration of disclosure efforts with appropriate oversight mechanisms and incentive structures.Theoretical Contribution: This study contributes to the theoretical discourse by offering conceptual insights and serving as a reference for future research on the role of social disclosure in mitigating child labor exploitation.Practical/Policy Implications: Practically, the findings can inform policymakers, particularly in considering the reinforcement of sustainability reporting regulations with a specific emphasis on social aspects.Limitations: This study is limited by its reliance on a literature review method, constrained to articles published within specific timeframes and academic databases.Keywords: child labor, social disclosure, sustainability accounting, child labor exploitation.